A mediating capacity: Towards an anthropology of the gut (Medicine Anthropology Theory, 2015)
In this article I seek to develop a conceptual framework for anthropological work on ‘the gut’ by bringing together reflections on ethnographic fieldwork on nutrition and well-being in KwaZulu-Natal, South Africa, with recent advances in the sciences of the gastroenterological and enteric nervous systems. While new evidence suggests that diet, immune system functioning, memory, and behaviour are shaped by the characteristics and processes of the enteric nervous system, it has also come into the public sphere as an object of intense disputation. Despite an ethnographic archive elaborating the diverse ways in which the gut contributes to well-being, it is still seen as a collection of folk systems incommensurable with scientific knowledge. I suggest that the mutual absorption of the natural and the social in the mediating membrane of the gut requires a more robust concept than either illness narrative or biosociality, and I ask: what would an anthropology of the gut look like?